In the tradition of Ahlfors-Bers, VII : 6th Ahlfors-Bers Colloquium, October 23-26, 2014, Yale University, New Haven, CT - Ahlfors-Bers Colloquium; Basmajian, Ara; Minsky, Yair Nathan; Reid, Alan W. (Contemporary mathematics, 2017)
The Ahlfors-Bers Colloquia commemorate the mathematical legacy of Lars Ahlfors and Lipman Bers. The core of this legacy lies in the fields of geometric function theory, Teichmuller theory, hyperbolic geometry, and partial differential equations. Today we see the influence of Ahlfors and Bers on algebraic geometry, mathematical physics, dynamics, probability, geometric group theory, number theory and topology. Recent years have seen a flowering of this legacy with an increased interest in their work.This current volume contains articles on a wide variety of subjects that are central to this legacy. These include papers in Kleinian groups, classical Riemann surface theory, Teichmuller theory, mapping class groups, geometric group theory, and statistical mechanics.